2007
DOI: 10.1007/s11782-007-0033-9
|View full text |Cite
|
Sign up to set email alerts
|

Leadership styles and employees’ job-related attitudes: An empirical study on the mediating effects of reciprocity and trust

Abstract: Reciprocity and trust are the basic principles of human social exchanges. Using a sample of 972 managers in China, we examined the relationship between transformational and transactional leadership styles and job-related attitudes of employees, as well as the mediating effects of both reciprocity and trust on the above relationship based on social exchange theory. The main findings of structural equation modeling analyses were shown as follows. Firstly, transformational leadership not only affects organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 66 publications
0
4
0
1
Order By: Relevance
“…Prior studies have conceptualized trust as a one-dimensional construct and ignored the other two important types of trust [36,37]. Modern developments in the trust literature have suggested two types of trust, cognitive trust (character based) and affective trust (relationship based), which makes a distinguished impact on employees' outcomes [11].…”
Section: Mediating Effects Of Cognitive and Affective Trust In The Rementioning
confidence: 99%
“…Prior studies have conceptualized trust as a one-dimensional construct and ignored the other two important types of trust [36,37]. Modern developments in the trust literature have suggested two types of trust, cognitive trust (character based) and affective trust (relationship based), which makes a distinguished impact on employees' outcomes [11].…”
Section: Mediating Effects Of Cognitive and Affective Trust In The Rementioning
confidence: 99%
“…Si les deux acteurs valorisent ce qu'ils reçoivent, le cycle d'échange se poursuivra et favorisera le développement d'un lien de confiance. À cet effet, plusieurs travaux, dont une étude portant sur les représentants syndicaux (Twigg et al, 2007), se sont inspirés de cette théorie des échanges sociaux pour expliquer les effets du leadership transformationnel (Doucet et al, 2008;Jia et al, 2007;Lo et al, 2010). Ces travaux font notamment valoir que ce type de leadership favorise des échanges de nature sociale en raison des composantes affectives qu'il mobilise.…”
Section: Le Leadership Transformationnel Et L'engagement Syndicalunclassified
“…The findings contradicted previous studies. Numerous studies have confirmed the importance of several leadership aspects on desired outcomes for both individual employee and organizational levels (Alfes, Truss, Soane, Rees and Gatenby, 2013;Babcock-Roberson and Strickland, 2010;Dvir et al, 2002;Hassan and Hatmaker, 2014;Jia et al, 2007;Jiao et al, 2013;Liaw et al, 2010). However, several authors suggested that further studies are needed to explain how this LMX actually works in the real situations (Graen and Uhl-Bien, 1995;Johnson et al, 2009;Sun et al, 2013).…”
Section: Discussionmentioning
confidence: 99%